INTERACTION PATTERNS TEACHER AND STUDENS AGAINST STUDENT IN LEARNING BEHAVIOR SOCIOLOGY SMAN 1 NEW KOTO DHARMASRAYA, THESIS. SOCIOLOGY OF EDUCATION STUDIES PROGRAM, STKIP PGRI WEST SUMATERA. PADANG, 2014 - Anora, Gira Meta; Adiyalmon, Adiyalmon; Husnita, Liza (Pendidikan Sosiologi, 2014)
In the learning process is more dominant sociological patterns of interactions using a one-way interaction centered on the teacher . This can be seen in the sociology of the learning process ongoing in the classroom during a lesson that teachers play an active role in the classroom, while the students just accept what is presented by the teacher . Conditions such as these have an impact on student behavior . Ideally, the learning pattern is an effective interaction that involves students actively as asked, an opinion, an idea / ideas and answer questions from the teacher. The purpose of this study was to describe patterns of interaction with student teachers on student behavior in the learning process sociology at SMA N 1 New Koto Dharmasraya. The theory used in this study is the theory of constructivism, where learning is a process to build knowledge through real experiences from the field. This study used a qualitative approach with descriptive type. In this study, the determination of informants conducted by purposive sampling technique, while the informants in this study were, sociology subject teachers, and students. The data collected in this study is primary data and secondary data.The unit of analysis is the group with the analysis of the data comprising the steps of reduction, data presentation / analysis of data,andconclusions .The results of this study are :patterns of interaction that are used or applied in learning patterns of interaction is one-way, two-way interaction pattern and multidirectional interaction patterns. With a one -way interaction patterns of students are not motivated to learn and there is no response from the students. With two-way interaction pattern , obtained feedback from the students, such as asking and answering questions from the teacher. With multi-way interaction of students actively in the learning process as an opinion, idea.